2007
DOI: 10.1111/j.1365-2419.2007.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical modelling of larval drift, growth and survival for the prediction of anchovy (Engraulis encrasicolus) recruitment in the Bay of Biscay (NE Atlantic)

Abstract: Fish recruitment is the result of the integration of small-scale processes affecting larval survival over a season and large oceanic areas. A hydrodynamic model was used to explore and model these physical-biological interaction mechanisms and then to perform the integration from individual to population scales in order to provide recruitment predictions for fisheries management. This method was applied to the case of anchovy (Engraulis encrasicolus) in the Bay of Biscay (NE Atlantic). The main data available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 31 publications
4
61
2
Order By: Relevance
“…Maillet & Checkley 1991, Baumann et al 2006a, Allain et al 2007. Recently, Hinrichsen et al (2010) used generalised additive model (GAM) analysis to compare daily increment widths with environmental parameters and identify the environmental factors that affect the growth rate of larval Baltic sprat Sprattus sprattus.…”
Section: Introductionmentioning
confidence: 99%
“…Maillet & Checkley 1991, Baumann et al 2006a, Allain et al 2007. Recently, Hinrichsen et al (2010) used generalised additive model (GAM) analysis to compare daily increment widths with environmental parameters and identify the environmental factors that affect the growth rate of larval Baltic sprat Sprattus sprattus.…”
Section: Introductionmentioning
confidence: 99%
“…Factors such as the NAO (albacore, Arregui et al 2006;sardine, Alheit & Hagen 1997; several fish stocks, mammals and seabirds, Hemery et al 2008), EA pattern (anchovy, Borja et al 2008); temperature anomaly (hake, Fernandes et al 2010), upwelling strength (anchovy, Borja et al 2008), turbulence (anchovy, mackerel and hake, Borja et al 1998, Allain et al 2007, Fernandes et al 2010, river discharge (anchovy, Planque & Buffaz 2008) and Ekman transport (anchovy, Irigoien et al 2008) have been shown to have significant effects on the recruitment or abundance of these species.…”
Section: Relationships Between Climate and Fishesmentioning
confidence: 99%
“…A study by Cermeño et al (2008) found a maximum average increment width of 18 µm day -1 for the period of 40 to 60 days after hatching, similar to those measured in the present study. However, Allain et al (2003Allain et al ( , 2007 showed an average maximum growth increment of 12 µm day -1 for 40 to 50 days after hatching. Although the difference in otolith growth between these studies is evident, a comparison is not possible as the criteria employed by Allain et al (2003Allain et al ( , 2007 to interpret the otolith daily increment are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, Allain et al (2003Allain et al ( , 2007 showed an average maximum growth increment of 12 µm day -1 for 40 to 50 days after hatching. Although the difference in otolith growth between these studies is evident, a comparison is not possible as the criteria employed by Allain et al (2003Allain et al ( , 2007 to interpret the otolith daily increment are unknown. However, it is likely that the observed difference between these studies is related to the different interpretation criteria.…”
Section: Discussionmentioning
confidence: 99%